Friction [compact disc, unabridged] - Brown, Sandra, 1948- (Hachette Audio, 2015)
A Texas Ranger, relegated to deskwork due to past recklessness, petitions to regain custody of his five-year-old daughter, and his case is assigned to a family court judge who is as attractive as she is ambitious. When a masked gunman barges in during the custody hearing with his sights on the judge, the Ranger reacts instinctually and goes after him. Will this take-charge lawman jeopardize his chances of custody by going after the would-be assassin?